Pengaruh Dewan Komisaris Independen Dan Kepemilikan Pihak Luar Terhadap Internet Financial Reporting Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2019 - Apsarida Mila Puspa; Heru Sulistiyo; Sam'ani Sam'ani (Universitas Ngudi Waluyo, 2021)
This research on Internet Financial Reporting aims to examines the influence of independent board of commissioners and the external ownership on Internet Financial Reporting with profitability as an intervening. The research population is manufacturing companies that are listed on the Indonesia Stock Exchange in 2019. Samples in this research selected through purposive sampling, so that obtained by sample as many as 122 companies. Statistical test tool uses path analysis. The results showed that independent board of commissioners influenced significantly and positively toward profitability, the external ownership had positive and not significant effect on profitability, independent board of commissioners and profitability had positive and significant effect on Internet Financial Reporting, and the external ownership had negative and not significant effect on Internet Financial Reporting. This research showed there is influence of independent board of commissioners on Internet Financial Reporting through profitability as an intervening variable, but there is no influence of the external ownership on Internet Financial Reporting through profitability as an intervening variable.